Carbapenem- and Colistin-Resistant Enterobacter cloacae from Delta, Colorado, in 2015 - Norgan, Andrew P. (Antimicrob Agents Chemother, 2016)
Resistance to carbapenems in Enterobacteriaceae is a clinical problem of growing significance. Difficulty in treating multidrug-resistant Gram-negative organisms with conventional antibiotics has led to a renewed and increasing use of polymyxin compounds, such as colistin. Here, we report the isolation of carbapenem- and colistin-resistant Enterobacter cloacae from a polymicrobial lower extremity wound in an ambulatory patient. Whole-genome sequencing demonstrated the presence of chromosomal bla(IMI-1) and bla(AmpC), as well as numerous efflux pump genes.